1989
DOI: 10.1007/bf00014305
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short-term laboratory pH depressions on molting, mortality and major ion concentrations in the mayflies Stenonema femoratum and Leptophlebia cupida

Abstract: Field surveys of the distribution of mayfly nymphs suggest that Stenonema femoratum are more acid-sensitive than Leptophlebia cupida. To assess whether this apparent difference in sensitivity of nymphs is reflected in differences in the degree of whole-body loss of [Na], [Cl], [Ca] or [K] under laboratory conditions, we exposed nymphs of both species to low pH for 96-192 h in soft water ([Ca] = 0.1 mM). Although mortality and loss of whole-body [Na] and [Cl] occurred in both species at pH 3.5, unexpectedly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
2
12
0
2
Order By: Relevance
“…a.) und wurde fur die Eintagsfliegen Stenonema und Leptophlehia durch Neutronenaktivierung indirekt bewiesen (ROWE et al 1989). …”
Section: Diskussionunclassified
“…a.) und wurde fur die Eintagsfliegen Stenonema und Leptophlehia durch Neutronenaktivierung indirekt bewiesen (ROWE et al 1989). …”
Section: Diskussionunclassified
“…However, Rowe et al (1989) found that nymphs within the size range of 2-14 mg dry wt showed no size related ion losses at pH 3.5.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers propose the use of molting, or exuviae production, as a method of determining sublethal responses in laboratory mayfly tests (Henry et al 1986;Pontasch et al 1989;Giesy et al 1990;Diamond et al 1990Diamond et al , 1992, while others have observed molting response to be a poor indicator of dose-dependent responses (Kennedy et al 2004). It is also suggested that molting could be a response to handling stress, temperature change, or a mechanism for shedding certain pollutants which may be absorbed onto the exoskeleton or gill surfaces (Kormonday 1965;Smock 1983;Rowe et al 1989;Diamond et al 1992). The number of exuviae produced by I. bicolor over a 7-day test period was calculated, along with geometric means and incipient response values at the concentration where 25 % of organisms showed inhibited growth (IC 25 ) ( Table 3).…”
Section: Exuviae As a Sublethal Growth Endpointmentioning
confidence: 97%